HERBAL APPROACH FOR INDUCING MULTIPLE FOLLICULAR DEVELOPMENT IN CROSSBRED COWS - KUMAR , S SATHESH; PUNNIAMURTHY, N (The Indian Journal of Animal Reproduction, 2023)
The objective of the study was to assess the efficacy of fresh indigenous herbs in inducing multiple folliculardevelopment in crossbred cows. Healthy and regularly cyclic crossbred cows (n=6) were utilized for the study. Asa control study, PGF20 (25 mg; IM) was administered to all the cows on Day 14 (Day 0-estrum) of the cycle. In thesubsequent natural cycle, fresh wet mash of Mi.Jrraya koenigiileaves (200- 300 g /day) and Pedalium murex (50g /day) were administered daily (per os) in equally split doses at-12 h interval, for seven days starting from Day 9of the cycle. Sap of Aloe vera leaves (100 g; per os; b. i.d) was administered for the first two days and PGF2" (25mg; IM) was administered on the penultimate day (Day 14) of herbal treatment. The ovarian status was assessedultrasonically.for the presence of large follicles(.::: 9 mm) on the day of PGF2a induced estrus in both control andherbal treated cycles. All the animal.s ( 100%) responded for the herbal treatment with ~ 2 large follicles. The meannumbers of large follicles on the day of induced estrus in control and treated cycles were 1.25 .:!:. 0.50 (1-2) and3.67 ± 1:37 (2-5) respectively with a mean diameter of 10.11.±.0.40 mm and 9.38± 0.31 mm respectively. fromthe study it was evident that the multiple follicular development could be effectively achieved using the abovecombination of herbs.
Keywords: Multiple tolicular; evelopment; Herbal approach; Cows